Optimized communication during risk disclosure to reduce nocebo headache after lumbar puncture—a study protocol for a randomized controlled clinical trial - Asan, Livia; Gronen, Johanna Sophie; Peters, Lorenz; Kleinschnitz, Christoph; Holle-Lee, Dagny; Benson, Sven; Bingel, Ulrike (Frontiers in Psychology, 2025)
Risk communication has been found to be a driver of nocebo effects in medical settings by enhancing negative expectations. In fact, merely disclosing the risk of side effects and complications of treatments or medical procedures increases reports of adverse events. Along these lines, it has been proposed that the occurrence of headache after lumbar puncture (LP), a routine diagnostic procedure in neurology, is caused to a large degree by the information delivered by the physician during the informed consent procedure. As withholding information conflicts with principles of patient autonomy, strategies are needed to mitigate nocebo-associated headaches without omitting the disclosure of risks. Here, we present a detailed study protocol for a preregistered, prospective, double-blind, randomized controlled clinical trial with N = 80 inpatients at the neurology department of the University Hospital Essen who have an indication for a diagnostic LP. The trial is designed to test whether optimized communication strategies aimed at minimizing nocebo effects during the informed consent procedure reduce headache-related impairment after LP compared to standard-of-care. Secondary outcomes include expectation of side effects, state anxiety, headache intensity and duration, use of on-demand pain medication, perceived warmth and competence of the physician, and satisfaction with the procedure.